Osteomyelitis in immunocompromised children and neonates, a case series - Foong, Bryan (2022)
Background: Osteomyelitis in immunocompromised children can present differently from immunocompetent children and can cause devastating sequelae if treated inadequately. We aim to review the aetiology, clinical profile, treatment and outcomes of immunocompromised children with osteomyelitis. Methods: Retrospective review of all immunocompromised children aged < 16 years and neonates admitted with osteomyelitis in our hospital between January 2000 and January 2017, and referred to the Paediatric Infectious Disease Service. Results: Fourteen patients were identified. There were 10 boys (71%), and the median age at admission was 70.5 months (inter-quartile range: 12.3–135.0 months). Causal organisms included, two were Staphylococcus aureus, two were Mycobacterium bovis (BCG), and one each was Mycobacterium tuberculosis, Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Burkholderia pseudomallei and Rhizopus sp. One patient had both Clostridium tertium and Clostridium difficile isolated. Treatment involved appropriate antimicrobials for a duration ranging from 6 weeks to 1 year, and surgery in 11 patients (79%). Wherever possible, the patients received treatment for their underlying immunodeficiency. For outcomes, only three patients (21%) recovered completely. Five patients (36%) had poor bone growth, one patient had recurrent discharge from the bone and one patient had palliative care for underlying osteosarcoma. Conclusions: Although uncommon, osteomyelitis in immunocompromised children and neonates can be caused by unusual pathogens, and can occur with devastating effects. Treatment involves prolonged administration of antibiotics and surgery. Immune recovery also seems to be an important factor in bone healing.